Comparative life-cycle assessment of novel steel section design with wire arc additive manufacturing - Arrè, Lidiana; Pagone, Emanuele; Laghi, Vittoria; Martina, Filomeno; Palermo, Michele (Springer, 2025)
Additive manufacturing, particularly Wire Arc Additive Manufacturing (WAAM), is emerging as a promising technology in the construction sector due to its potential to reduce environmental impacts. Life-Cycle Assessment (LCA) is a crucial methodology for evaluating the environmental footprint of products and processes that can be carried out from raw material extraction to the end of production, commonly referred to as “cradle-to-gate” analysis. This study focuses on the environmental impact of 3D-printed steel elements using WAAM technology for construction applications. Specifically, the conventional production of Circular Hollow Section (CHS) steel components was compared with the innovative production of Tubular Sandwich Section (TSS) steel components using WAAM. The analysis provides a comparison of the carbon footprint associated to both production methods, highlighting in detail the emission factors associated with each step of the WAAM production. The results highlighted that WAAM not only offers design and structural benefits to build complex-shaped geometries but also contributes to more sustainable construction practices with a lower “cradle-to-gate” carbon footprint due to the reduced material consumption associated with material efficiency.
Keywords: 33 Built Environment and Design; 4104 Environmental Management; 40 Engineering; 41 Environmental Sciences; 4014 Manufacturing Engineering; 3302 Building; 12 Responsible Consumption and Production; Additive Manufacturing; Sustainability; Iron and Steel